Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean - Lundsten, Lonny; Reiswig, Henry M.; Austin, William C. (Zootaxa, 2017)
Carnivorous feeding among the Cladorhizidae (Porifera, Demospongiae, Poecilosclerida) was first documented in 1995. Since that time, 161 species have been described and are currently recognized in 9 genera. Cladorhiza is the most speciose genus with a global, deep-water distribution of 41 species. Here we describe three new Cladorhiza species of ‘crinorhiza’ form from the Northeast Pacific Ocean off California, USA, and the Gulf of California, Mexico, from depths of 2472–4100m. In total, 11 specimens were collected between 1969 and 2015. Video recordings from remotely operated vehicles yield additional information on habitat type, geographic distribution, and abundance for some of these species.